Flood impact on urban roads and commuting: A case study of Wuhan, China - Yaolin Liu; Yaolin Liu; Yaolin Liu; Hongxin Zhang; Huiting Chen; Cuizhen Chen (Frontiers in Environmental Science, 2022)
Rainfall events have become more frequent and more serious, leading to rampant floods. Floods in urban areas greatly impair the serviceability of the transport system and cause disruption to commuting. However, little is known about the commute response under various rainfall scenarios in developing country cities despite the uncertainty of climate change. A high-resolution flood modeling module and a commute simulation module were integrated to examine the impact on commuting under floods. Flood maps under three rainfall scenarios with increasing rainfall intensity and duration were obtained, and road vulnerability was assessed considering the speed drop. We innovatively employed location-based service big data to perform commute simulation under floods based on the shortest time cost principle. The results show that a large amount of passable but affected commuters become disconnected commuters as the rainfall intensity increases. Also, commute loss of each traffic zone would not increase linearly, which means that the emphasis and strategy of disaster prevention and mitigation are not the same in different rainfall scenarios. We integrated hot spots of flood exposure, road vulnerability, and commuting loss and found that there was inconsistent spatial distribution between the three indicators. This indicates that areas need to take different measures according to the local damage characteristics. This work studied the relationship between severe weather conditions and commuting activity performance at the city level and has important practical guiding significance for building resilient cities.